Quebra-quebra de 1942: um dia para lembrar - Freire, Carlos Renato Araújo (2014)
This text analyzes the History of Memory of the clash referred to as “Quebra-quebra” that took place on August 18th 1942 from the fortieth and fiftieth anniversary of World War II. Despite the retrospective importance that we assign to the event as one of the factors responsible for pressuring the government of Getúlio Vargas to declare war on the Axis powers, only from the 1980s are there intensifying eruptions of investments in memory that transform the depredations of the commercial establishments that had some relation to the Axis (Germany, Italy and Japan) in an event through its share in newspaper reports, memoirs, photographs, restoration and construction of monuments. Specifically analyzing memory investments of Thomaz Pompeu Gomes de Matos, Alberto Santiago Galeno, Stênio Azevedo, Geraldo Nobre and memories of some families of descendants of harmed immigrants, it intends to discuss the uses of the past in the present proposing questions about the relationships between individual memory and collective memory, the interaction between the past event and the present of utterances and the interweaving of the temporalities in the formalization of narratives that day processes. The event is seen here not as a surface environment, but rather as a way to observe the interweaving of possibilities in the present tense, not as an immutable data but as indefinite, uncertain and open to new configurations of meaning and significance.